Analysis of the YouTube content management aimed at children: a case study - Neira Placer, Paula; Visiers Elizaincin, Ana (Estudios sobre el Mensaje Periodístico, 2023)
An attractive audience for content managers on YouTube is children. Numerous channels have appeared aimed at this type of viewer, some of them with millionaire audiences as the Spanish YouTube channel of Vlad and Niki. Knowing how a channel with such a successful audience is managed can provide interesting insights for content managers. This case study analyses the content published on the channel from its opening in December 2018 until February 2021. The research suggests that managers, with the aim of reaching a mass audience and obtaining brands to sponsor their account, modified the frequency and quantity of content, its duration, and even increased control in the production of content by contextualising it in environments with less recording issues and more scripted stories.
Keywords: YouTube; social networks; childhood; content management; brand